Sealing the fate of arctic marine mammals : challenges and opportunities of non-legislative international organisations - Suslina, Anastasiia (SLU/Dept. of Urban and Rural Development, 2021)
The Arctic is changing rapidly as a result of climate change, putting endemic marine mammal species in greater danger than ever. In such circumstances, the management process in international organizations becomes more urgent. The Arctic Council and the North Atlantic Marine Mammal Commission are two international non-legislative bodies that manage marine mammals in the Arctic region. The challenges that organizations encounter are examined using the "What is the Issue Represented to be?" analytical framework based on interviews with experts in this field. Two central problems are addressed in detail: the Arctic Council's loss of control over the Arctic states' domestic policies and insufficient guidance provided by the ecosystem-based management approach that both organizations are using. The primary conclusion is that there is a need for a stronger feedback mechanism within the Arctic Council, as well as collaborative deepening the ecosystem-based approach and integrating indicators to track successes of the working processes.